2007
DOI: 10.1080/03069880601106831
|View full text |Cite
|
Sign up to set email alerts
|

‘If you don't want to tell anyone else you can tell her’: young people's views on school counselling

Abstract: The aim of the research was to assess the views of young people about school counselling. In total, 415 pupils from five secondary schools took part in the survey. A smaller number of these pupils took part in focus groups (n 0/9) to explore their views in more depth. In general, the young people seemed to value having a school counsellor. Most were aware of the school counselling service, although a substantial number (21%) indicated a lack of awareness. For many who were aware, their knowledge of the service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(106 citation statements)
references
References 13 publications
7
95
0
4
Order By: Relevance
“…Tento článek se nechal inspirovat celou řadou zahraničních výzkumů (Howieson, Semple, 2000, Fox, Butler, 2007, Boulton et al, 2007 a interpretuje výsledky realizovaného výzkumného šetření, které se zaměřuje na výchovné poradenství očima žáků základních škol. Může pomoci objevit pohled mladé generace na práci výchovných poradců ve školách a orientovat se v něm.…”
Section: úVodunclassified
See 2 more Smart Citations
“…Tento článek se nechal inspirovat celou řadou zahraničních výzkumů (Howieson, Semple, 2000, Fox, Butler, 2007, Boulton et al, 2007 a interpretuje výsledky realizovaného výzkumného šetření, které se zaměřuje na výchovné poradenství očima žáků základních škol. Může pomoci objevit pohled mladé generace na práci výchovných poradců ve školách a orientovat se v něm.…”
Section: úVodunclassified
“…Mohou narušovat také školní život a bránit efektivnímu vzdělávání (Fox, Butler, 2007). Přitom právě školní prostředí je jedno z nejdůležitějších, kde by se mělo odehrávat preventivní působení, které předchází vzniku deviantního chování dětí a mládeže.…”
Section: Výchovné Poradenství a Jeho Vztah K Sociální Pedagogiceunclassified
See 1 more Smart Citation
“…: 21). Fox and Butler (2007) examined young people's views on school counselling and found that young people do value having counsellors in schools. However, they also pointed to a range of issues that needed to be taken into account by those who manage school counselling services, including 'how counselling services become more accessible and acceptable to young people' (ibid.…”
Section: Plr0809/115mentioning
confidence: 99%
“…• the effectiveness of school counselling services (Cooper, 2004; • the views of school staff attitudes to counselling (Cooper et al, 2005;Baginsky, 2003) • the views of young people about school counselling (Fox and Butler, 2007) • models of counselling service delivery (Pattison et al, 2008). Cooper (2004Cooper ( , 2006 indicates that school counselling interventions are beneficial to young people, including a reduction in psychological distress, and thus increases in psychological wellbeing as a result.…”
Section: Plr0809/115mentioning
confidence: 99%